2005
DOI: 10.1111/j.1745-7254.2005.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism and regulation of autophagy1

Abstract: Autophagy is a major cellular pathway for the degradation of long-lived proteins and cytoplasmic organelles in eukaryotic cells. A large number of intracellular/extracellular stimuli, including amino acid starvation and invasion of microorganisms, are able to induce the autophagic response in cells. The discovery of the ATG genes in yeast has greatly advanced our understanding of the molecular mechanisms participating in autophagy and the genes involved in regulating the autophagic pathway. Many yeast genes ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
163
0
10

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(175 citation statements)
references
References 127 publications
(138 reference statements)
2
163
0
10
Order By: Relevance
“…26 When MDA-MB231 cells were coincubated with 8.45 μM JAHA and 1 nm rapamycin, by analogy with BHT treatment, we found that also this cotreatment was capable of reversing the JAHAtriggered decrease in cell number (Figure 9), thereby revealing autophagy inhibition as a further aspect, supplementary to early ROS production, involved in the cytotoxic effect exerted by the HDACi under study on MDA-MB231 breast tumor cells.…”
Section: ■ Resultsmentioning
confidence: 99%
“…26 When MDA-MB231 cells were coincubated with 8.45 μM JAHA and 1 nm rapamycin, by analogy with BHT treatment, we found that also this cotreatment was capable of reversing the JAHAtriggered decrease in cell number (Figure 9), thereby revealing autophagy inhibition as a further aspect, supplementary to early ROS production, involved in the cytotoxic effect exerted by the HDACi under study on MDA-MB231 breast tumor cells.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Autophagy starts with the formation of an autophagosome, enclosed within a double membrane that engulfs part of cytoplasm. The formation of autophagosome depends upon Atg proteins [34]. Autophagy can be stimulated by various stresses, including nutrient depletion or hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Although autophagy and autophagy-related processes are dynamic, they can be broken down into several discrete steps for the purpose of discussion: (1) induction, (2) autophagosome formation, (3) autophagolysosome formation, and (4) delivery and degradation of the autophagic body [1] . Autophagy is induced as a response to both extracellular stress conditions (nutrient deprivation, hypoxia, and oxidative stress) and intracellular stress conditions (endoplasmic reticulum stress, accumulation of damaged organelles, and aggregation of proteins).…”
Section: Mechanisms and Pharmacologic Targeting Of Autophagymentioning
confidence: 99%
“…Autophagy is a universal, dynamic process that takes place in all eukaryotic cells. There are three primary forms of autophagy: macroautophagy, microautophagy and chaperone-mediated autophagy [1] . Of these classifications, macroautophagy, herein referred to as autophagy, is the major form of autophagy and has been well characterized in recent years.…”
Section: Introductionmentioning
confidence: 99%